Administration of G-CSF for PBSC collection may unmask pre-existing IgA-nephropathy: A case report - Obereisenbuchner, Florian; Bader-Zollner, Sabine; Schobel, Hans-Paul (Journal of Clinical Nephrology, 2022)
It is utterly important to ensure the safety of stem cell donors and limit the incidence of long-term adverse events. Additionally, the willingness to donate the potentially life-saving stem cells, depends among other reasons, on the donor’s trust in the safety of the procedure as our case highlights. Here we present the case of a 35-year-old patient who developed macrohematuria and proteinuria following peripheral blood stem cell (PBSC) donation. 4 years later he was diagnosed with IgA-nephropathy (IgAN) and the disorder was causally attributed to the PBSC donation. He discouraged his family and friends from registering as donors because of this. In the current case report, we review the literature on the relationship between IgAN and PBSC donation and suggest under which conditions stem cell donation can still be performed even with a prior diagnosis of IgAN.